Legal Protection of Industrial Designs: A Case Study on â€œLurikâ€ in Klaten, Indonesia - Anita Widya Putri; Inayah Inayah (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The protection of traditional culture plays a good role in providing support to the community in preserving traditions, including in the design work of the lurik product industry. The problems with lurik design in Indonesia include the absence of a business climate that fully provides legal protection. It does not rule out apathy towards perceptions of legal provisions, because what is happening now is that the community concerned has the view to meet their daily needs easily. The method used in this research is juridical empirical research method, research on the effectiveness of law is a study that discusses how the law operates in society. This research is descriptive in nature which provides a systematic and comprehensive description of the legal protection of the lurik product design industry in Klaten Regency and the level of legal awareness of the lurik designers in Klaten Regency. The results of the study show that the legal protection efforts for the design of the lurik product industry in Klaten are quite good, but regarding legal protection against lurik as a cultural heritage there is no law regulating it. The level of legal awareness of lurik designers in Klaten is still low, because designers are still reluctant to register industrial designs. The aspects of creation, legal protection, management and utilization of intellectual property in the field of industrial design can form an intellectual property ecosystem with the aim that intellectual property can speak in an economic and social context, and create a correlation between economic goals, development priorities, state resources based on welfare by utilizing intellectual property, especially in the field of striated product industrial design.